Effects of incubating an acid sulfate soil treated with various liming materials under submerged and moist conditions on pH, Al and Fe - A. K., Rosilawati; J., Shamshuddin; C. I., Fauziah (Academic Journals, 2014)
Acid sulfate soil in Malaysia is known to be very acidic with pH < 3.5 and have high amount of aluminum. A study was conducted to investigate the efficacy of various lime sources for alleviating the infertility of the soil and to determine its lime requirement. The treatments were ground magnesium limestone, hydrated lime, liquid lime and fused magnesium phosphate under submerged and moist condition for 3 months. Soil and water were sampled throughout the incubation period for the determination of pH, Al and Fe. The initial soil pH and exchangeable Al were 3.43 and 7.71 cmolc kg-1, respectively. After 3 months of incubation under submerged condition, the soil pH and water pH increased from 3.43 to 5.01 and from 2.38 to 5.17, respectively. Under moist condition, the pH increased from 3.43 to 4.02 due to application of 6 t ground magnesium limestone (GML) ha-1. The efficacy of hydrated lime as soil ameliorant was comparable to that of GML. It was recommended that 6 t ha-1 of GML be applied prior to the growing season for maximum benefit. This study showed that GML can be effectively applied to ameliorate the infertility of acid sulfate soils for rice cultivation.